RELACIJE ANTROPOMETRIJSKIH KARAKTERISTIKA I SITUACIONO-MOTORIČKIH SPOSOBNOSTI RUKOMETAŠA - Fahrudin Mavrić; Hasim Mekić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
Handball belongs to sport's games, which demand, and contemporary influence on development of constitutional characteristics, functional abilities of all organic systems as well as mobility and situation-mobility abilities. This can be achieved by training process and by selection, which can be conveyed from the beginning of go in for sports till the end of sport's carrier. We convey this through different selection shapes, starting from spontaneous, through ones. The research of anthropological space in the World is part of mosaic, which has to be made necessarily, so we would have a possibility to perform selection more precisely and to manage training process. Anthropometrical characteristics and situation-mobility abilities are part of anthropological space that is in the function of achieving success in handball. The subject of this research presents certain anthropometrical and situation-mobility parameters of young handball players and their mutual relations The aim of this research is relation of anthropometrical characteristics situationmobility abilities of handball players. The research was conveyed on a sample of young handball players whose age was boarded from 14 till 16, and the total number of examiners was 70 handball players from Southeast Serbia. On the basis of these results, it can be concluded that the maximal causality between anthropometrical characteristics and situation-mobility abilities was explained with a pair of canonical functions. Correlation is rather high and its amount is 69 and gained function is almost 47% of common variability